VR-Assisted Environmental Education for Undergraduates. (15th October 2022) - Ruan, Bibo
Abstract : Environmental education is an important approach to improve students' environmental literacy. The method of environmental education in colleges and universities is advancing with the development of multimedia technologies, among which virtual reality (VR) technology is gradually being widely applied to education due to its strong sense of immersion and interactivity. This article focuses on the application of VR technology to environmental education in colleges and universities, using EduVenture APP and VR glasses to innovate environmental education, with the aim of improving students' performance and making a strong connection between sense and activity of environmental protection. This research found that the learning efficiency and the sense of environmental protection of students were enhanced with VR assistance in comparison to traditional instruction, and students' learning interest in environmental protection activity was also improved.